Dynamics of a continued fraction of Ramanujan with random coefficients. (30th June 2005) - Borwein, Jonathan M.; Luke, D. Russell
Abstract : We study a generalization of a continued fraction of Ramanujan with random, complex-valued coefficients. A study of the continued fraction is equivalent to an analysis of the convergence of certain stochastic difference equations and the stability of random dynamical systems. We determine the convergence properties of stochastic difference equations and so the divergence of their corresponding continued fractions.